How strong is your firm's competitive advantage?. - Marburger, Daniel (New York : Business Expert, 2012)
Perhaps the most confounding characteristic of the competitive marketplace is that everyone wants a piece of the action. If a firm successfully enters a new market, creates a new product, or designs new innovations for an existing product, its just a matter of time before competitors follow suit. And the influx of competition inevitably places downward pressure on both price and profitability. But the speed at which competitors invade ones market is not the same in all industries; some are more resistant to the forces of competition than others. In 1979, Harvard economist Michael Porter theorized his Five Forces Model (updated in 2008). The Five Forces Model identifies the characteristics that can help insulate a firm from competitive forces. For the firm that seeks to put together a business plan, or for the firm that is considering opportunities for diversification, an understanding of the Five Forces Model is essential.
Keywords: Strategic planning; Competition; Virksomhedens konkurrenceevne; Erhvervs{uBBEE}omi.